Experimental research and application of old combined bridge barriers with non-standard sections - He, Guomeng; Ren, Yanhong; Sun, Chun; Deng, Yong; Tan, Yan; Deng, Qichuan; Wang, Chenghu; Bu, Qianmiao (Frontiers in Materials, 2022)
To improve the protective performance of old combined bridge barrier with non-standard section, this paper has improved the guardrail scheme. The newly improved guardrail is evaluated by finite element simulation, yield line theory calculation and a crash test to see whether it reaches class SA protection. The results show that the blocking, redirecting, and buffering functions of the improved scheme meet the Standard for Safety Performance Evaluation of Highway Barriers (JTG B05-01-2013), and its protection class reaches class SA. The bridge barrier with strict deformation control cannot be evaluated by the yield line theory calculation alone. Thus, the evaluation should be assisted with finite element simulation and a crash test. The improved scheme has been successfully applied to engineering practice. With simple construction, safety, and reliability, the scheme effectively reduces engineering costs and improves the protective performance of old combined bridge barriers with non-standard section.